The Implementation of the Book Nahwu Al-Wadhih in Grammar Learning to Enhance the Proficiency in Reading Classic Arabic Literature - Maghfiroh, Debi; Sofa, Ainur Rofiq; Sugianto, Muhammad (Universitas Muhammadiyah Sumatera Barat, 2025)
Nahwu learning (Arabic grammar) is one of the most crucial aspects of Arabic language education, especially in the pesantren (Islamic boarding school) environment. The study of Qowaid Nahwu is a fundamental component in understanding Arabic grammar, particularly in reading Kutub At-Turats within pesantren. To this day, the study of Kutub At-Turats remains the primary source of learning in pesantren and is regarded as essential religious knowledge that must be studied and practiced. This research aims to analyze the implementation of the Nahwu Al-Wadhih book in teaching Qowaid Nahwu at Pondok Pesantren Al-Mashduqiah and its effectiveness in enhancing proficiency in reading Kutub At-Turats. Pondok Pesantren Al-Mashduqiah is a modern Islamic boarding school that uses Nahwu Al-Wadhih as its primary instructional material for Qowaid Nahwu. The research employs a qualitative approach using observation, interviews, and documentation techniques. The findings indicate that the use of Nahwu Al-Wadhih, which adopts the inductive method (Al-Istiqrâ’iyyah), effectively helps students comprehend grammatical rules systematically. This method is particularly beneficial for beginner Arabic learners as it encourages them to construct their own sentences rather than merely memorizing theoretical concepts. Furthermore, this approach enhances syntactic analysis skills, enabling students to read and understand Kutub At-Turats more proficiently. Thus, the implementation of Nahwu Al-Wadhih has proven effective in improving Arabic text-reading skills within the pesantren environment.